Prognostic value of forward flow indices in primary mitral regurgitation due to mitral valve prolapse - Petolat, Elisabeth; Theron, Alexis; Resseguier, Noemie; Fabre, Cyprien; Norscini, Giulia; Badaoui, Rita; Habib, Gilbert; Collart, Frederic; Zaffran, Stéphane; Porto, Alizée; Avierinos, Jean-François (Frontiers in Cardiovascular Medicine, 2023)
Background: Degenerative mitral regurgitation (DMR) due to mitral valve prolapse (MVP) is a common valve disease associated with significant morbidity and mortality. Timing for surgery is debated for asymptomatic patients without Class I indication, prompting the search for novel parameters of early left ventricular (LV) systolic dysfunction. Aims: To evaluate the prognostic impact of preoperative forward flow indices on the occurrence of postoperative LV systolic dysfunction. Methods: We retrospectively included all consecutive patients with severe DMR due to MVP who underwent mitral valve repair between 2014 and 2019. LVOTTVI, forward stroke volume index, and forward LVEF were assessed as potential risk factors for LVEF<50% at 6 months postoperatively. Results: A total of 198 patients were included: 154 patients (78%) were asymptomatic, and 46 patients (23%) had hypertension. The mean preoperative LVEF was 69±9%. In total, 35 patients (18%) had LVEF≤60%, and 61 patients (31%) had LVESD≥40 mm. The mean postoperative LVEF was 59±9%, and 21 patients (11%) had postoperative LVEF<50%. Based on multivariable analysis, LVOTTVI was the strongest independent predictor of postoperative LV dysfunction after adjustment for age, sex, symptoms, LVEF, LV end systolic diameter, atrial fibrillation and left atrial volume index (0.75 [0.62-0.91], p<0.01). The best sensitivity (81%) and specificity (63%) was obtained with LVOTTVI≤15 cm based on ROC curve analysis. Conclusion: LVOTTVI potentially represents an independent marker of myocardial performance impairment in the presence of severe DMR. LVOTTVI is an earlier marker compared with traditional echo parameters and aids in the optimization of the timing of surgery.